(untitled) (LEARNing Landscapes, 2023)
We analyzed the links between access to higher education, exams, and equity in education in Türkiye. Next, we made numerous recommendations and referred to a phenomenon: ”The Magnus Effect” to delve into the problems of the relevant processes. After conducting a review of the literature, we came up with four core sources that produce equity issues: tracking, stratification, socioeconomic status, and the qualifying elimination system. One of the ironies was that access to higher education institutions is enabled via high-stakes national exams, which seem to legitimize the process while leading to countless more inequities.